Effectiveness Of Abdominal Stretching Exercises On Reducing Dysmenorrhea In High School Students In East Aceh District - Nuri Putri Ayu; Jhon Roby Purba; Arini Clara Hutauruk (International Journal of Health Engineering and Technology, 2026)
Menstruation is a natural process in which the inner lining of the uterus (endometrium) is shed through the vagina. Menstruation often causes symptoms such as lower abdominal pain, constipation, diarrhea, thigh pain, breast tenderness, bloating, headaches, nausea, vomiting, backaches, fatigue, irritability, loss of balance, clumsiness, and disturbed sleep. In severe cases, symptoms such as inability to perform tasks or fainting can even occur. These symptoms are known as dysmenorrhea. Dysmenorrhea is painful menstrual flow. In school-aged adolescents, dysmenorrhea can significantly disrupt daily activities, sometimes requiring them to miss school. Abdominal stretching exercises are a physiotherapy intervention to reduce dysmenorrhea. The purpose of this study was to determine the effectiveness of abdominal stretching exercises in reducing dysmenorrhea in high school students in east aceh regency. This research design uses an experimental research method with one group pre and post test design. The sample size was 15 people. This study was conducted for 8 weeks with a frequency of 3 times a week and a duration of 10-15 minutes per exercise session. Pain measurement used nrs (numeric rating scale). The results of statistical analysis significantly showed a decrease in pain after the intervention p = 0.000 (p <0.05) with a mean value before the intervention of 7.51 ± 0.91 and after the intervention of 4.20 ± 0.86. The conclusion of this study is that abdominal stretching exercise is effective in reducing dysmenorrhea in high school students in east aceh regency.